Glucagon Like Peptide-1 Receptor Expression in the Human Thyroid Gland - Gier, Belinda (Endocrine Society, 2012)
BACKGROUND: Glucagon like peptide-1 (GLP-1) mimetic therapy induces medullary thyroid neoplasia in rodents. We sought to establish whether C cells in human medullary thyroid carcinoma, C cell hyperplasia, and normal human thyroid express the GLP-1 receptor. METHODS: Thyroid tissue samples with medullary thyroid carcinoma (n = 12), C cell hyperplasia (n = 9), papillary thyroid carcinoma (n = 17), and normal human thyroid (n = 15) were evaluated by immunofluorescence for expression of calcitonin and GLP-1 receptors. RESULTS: Coincident immunoreactivity for calcitonin and GLP-1 receptor was consistently observed in both medullary thyroid carcinoma and C cell hyperplasia. GLP-1 receptor immunoreactivity was also detected in 18% of papillary thyroid carcinoma (three of 17 cases). Within normal human thyroid tissue, GLP-1 receptor immunoreactivity was found in five of 15 of the examined cases in about 35% of the total C cells assessed. CONCLUSIONS: In humans, neoplastic and hyperplastic lesions of thyroid C cells express the GLP-1 receptor. GLP-1 receptor expression is detected in 18% papillary thyroid carcinomas and in C cells in 33% of control thyroid lobes. The consequence of long-term pharmacologically increased GLP-1 signaling on these GLP-1 receptor-expressing cells in the thyroid gland in humans remains unknown, but appropriately powered prospective studies to exclude an increase in medullary or papillary carcinomas of the thyroid are warranted.